RESTORASI MANAJEMEN WAKAF DARI TRADISIONAL MENUJU PROFESIONAL - Wawan Juandi; Nawawi Nawawi (LP2M Universitas Ibrahimy, 2020)
This study found that waqf is a form of worship that contains a distinct benefit. The distinction of waqf is that its object is permanent and its benefits continue to flow for the benefit of Islamic preaching and the economic improvement. Waqf is not only in the form of immovable objects but also includes all handy objects. This is in accordance with the words of the Prophet,